2019
DOI: 10.1111/tra.12635
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the assembly, integrity and maintenance of the endoplasmic reticulum‐peroxisome tether

Abstract: Organelle tethering and intercommunication are crucial for proper cell function. We previously described a tether between peroxisomes and the endoplasmic reticulum (ER) that acts in peroxisome population control in the yeast, Saccharomyces cerevisiae. Components of this tether are Pex3p, an integral membrane protein of both peroxisomes and the ER and Inp1p, a connector that links peroxisomes to the ER. Here, we report the analysis of random Inp1p mutants that enabled identification of regions in Inp1p required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
(88 reference statements)
0
11
0
Order By: Relevance
“…Inp1 is in the correct subcellular location to be a PM-PER tether During cell division, a subset of peroxisomes are retained by cortical anchoring in the mother cell (Fagarasanu et al, 2005;Hoepfner et al, 2001;Knoblach and Rachubinski, 2019;Knoblach et al, 2013). Though the role of the cER in peroxisome retention has been reported, the role of the plasma membrane remains unexplored.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Inp1 is in the correct subcellular location to be a PM-PER tether During cell division, a subset of peroxisomes are retained by cortical anchoring in the mother cell (Fagarasanu et al, 2005;Hoepfner et al, 2001;Knoblach and Rachubinski, 2019;Knoblach et al, 2013). Though the role of the cER in peroxisome retention has been reported, the role of the plasma membrane remains unexplored.…”
Section: Resultsmentioning
confidence: 99%
“…During the course of our study, an independent study reported a random Inp1 mutant in this motif (LXXLP). This mutant also blocked recruitment of Inp1 to peroxisomes and interfered with Inp1 function (Knoblach and Rachubinski, 2019).…”
Section: The Pex3 Binding Site Of Inp1 Resembles the Pex3 Binding Sitmentioning
confidence: 93%
See 2 more Smart Citations
“…S. cerevisiae Inp1 tethers peroxisomes to the cortex of mother cells, but also is important for capturing organelles in buds (Fagarasanu et al, 2005). Inp1 is a soluble protein that is recruited to peroxisomes by the PMP Pex3 (Munck et al, 2009;Knoblach et al, 2013;Knoblach and Rachubinski, 2019). It mainly associates to mature peroxisomes that are retained in mother cells.…”
Section: Introductionmentioning
confidence: 99%